Enhancing Accountability Mechanisms in NGT: Constitutional and Legisla tive Reforms - Gupta, Shivangi (Trinity Law Review, 2025)
The National Green Tribunal (NGT) was established as a specialized body to address  environmental disputes and ensure the effective enforcement of environmental laws  in India. However, challenges related to accountability and execution have often  impeded its ability to function optimally. This paper examines the accountability  mechanisms of the NGT within the framework of India’s constitutional provisions  and statutory mandates. It highlights the gaps in its current regulatory and  enforcement structures that hinder effective environmental governance. The study  explores relevant constitutional principles, such as the directive under Article 48A  to protect and improve the environment and the fundamental duty under Article  51A(g) to safeguard natural resources. Additionally, it critically evaluates the NGT’s  quasi-judicial status and the limitations imposed by legislative ambiguities and  inadequate administrative support. The paper proposes constitutional and legislative  reforms, including amendments to enhance the NGT’s powers for monitoring  compliance, increasing transparency and ensuring judicial review of its decisions.  By strengthening accountability mechanisms, the NGT can emerge as a more robust  institution capable of upholding environmental justice and addressing pressing  ecological concerns.
Keywords: protect; natural; dis putes; ensure; gaps; imposed